AN UNUSUAL CASE OF HORNER'S SYNDROME. (29th November 2012) - Pengas, G; Faris, C; Repanos, C; Hull, RG; Burke, G
Abstract : A 71-year-old man presented with headache for a month and left eyelid droop for 2 days. He complained of recurrent sore throat, weight loss and long-standing anorexia, depression, iron deficiency anaemia and was receiving methotrexate for rheumatoid arthritis. Examination revealed a left sided Horner's syndrome. He had palpable temporal arteries. He was cachectic and apyrexial. There was no other abnormality. Blood tests showed microcytic anaemia, CRP 100 mg/l and ESR 40 mm/h (previously normal). MRI brain and MRA of head and neck were initially reported as normal. There was no evidence of atlanto-axial subluxation/activity. CSF examination was normal. Within 2 weeks he represented with dysarthria, dysphagia and a left-deviating tongue. His CRP rose to 140 mg/l. He exhibited a left-sided Villaret's syndrome: cranial nerve 9, 10, 11, 12 palsies and Horner's syndrome. MRI with contrast showed a retropharyngeal enhancing mass involving the left carotid and hypoglossal canal. Biopsy found a large fibrous and necrotic area extending from one eustatian tube to the other without frank pus. Microscopy and culture was negative for tuberculosis, but grew diphtheroids, candida and E.coli. There was no malignancy. He received appropriate antibiotics and his headache and inflammatory markers have resolved. He has improved tongue movement, but his neurology otherwise remains unchanged. The final diagnosis was skull base osteomyelitis/abscess causing Villaret's syndrome. This constellation of lower cranial nerve palsies and Horner's syndrome always localises the lesion outside the skull.